Comparing Burnout in Sport-Specializing Versus Sport-Sampling Adolescent Athletes: A Systematic Review and Meta-analysis. Issue 3 (2nd March 2020) - Giusti, Nicolas E.; Carder, Seth L.; Vopat, Lisa; Baker, Jordan; Tarakemeh, Armin; Vopat, Bryan; Mulcahey, Mary K.
Background: The prevalence of adolescent athletes who specialize in sports has increased in recent years. Substantial literature on youth sports has linked early sport specialization to negative consequences, such as burnout and injury. However, empirical evidence directly comparing burnout rates in sport specialization versus sport sampling is very limited. Purpose: To conduct a systematic review and meta-analysis to evaluate psychological burnout in adolescent athletes who sport specialize compared with adolescent athletes who sport sample. Study Design: Systematic review; Level of evidence, 4. Methods: A systematic review was performed through use of the PubMed, SportDiscus, PsychInfo, and CINAHL databases (between inception and May 2019) according to PRISMA-IPD (Preferred Reporting Items for Systematic Reviews and Meta-Analyses of individual participant data) guidelines. Results from the 3 measures of the Athlete Burnout Questionnaire and athlete specialization status were recorded and analyzed. An athlete was determined to be a "sport specializer" if he or she met the following 3 criteria: (1) athletic participation limited to 1 sport, (2) which is competed in > 8 months in 1 year, and (3) to the exclusion of all other sports. Results: Of 3578 studies, 8 met criteria for final meta-analysis, which included 1429 athletes (mean age, 15.59 years; range, 12.5-17.2 years). Of these, 1371 (95.9%) were sport specializers, whereas 58 (4.1%) were sport samplers. A total of 1422 (99.5%) athletes completed the Athlete Burnout Questionnaire. Athletes who specialized reported higher levels of burnout than athletes who did not specialize. Specializers had a greater sense of reduced accomplishment (difference of means [△], 0.87; 95% CI, 0.67-1.08; P < .01). Specializers also reported greater exhaustion (△, 0.46; 95% CI, 0.24-0.68; P < .01) and sport devaluation (△, 0.41; 95% CI, 0.22-0.60; P < .01) than athletes who were samplers. Conclusion: Adolescent sport specialization was associated with greater levels of burnout in all 3 aspects (reduced sense of accomplishment, sport devaluation, and exhaustion) compared with sport sampling.